AN ANALYSIS OF STUDENTS’ PUNCTUATION IN WRITING RECOUNT TEXT - Dini Hadi Pratiwi; Tenia Ramalia (Journal of Education, Linguistics, Literature and Language Teaching, 2022)
The objectives of this research are to find out the types of errors’ punctuation and the dominant errors’ punctuation in students’ writing recount text at the eleventh grade of SMAN 14 Kabupaten Tangerang. The methodology of this research used a descriptive qualitative research, that was carried out on 32 students in class XI Bahasa 2 at the eleventh grade of SMAN 14 Kabupaten Tangerang. The data were collected from the results of students’ writing of recount text. The result of the research shows that types of errors of punctuation marks made by students are 88 or 91,67% errors in omission, 3 or 3,12% errors in addition, and 5 or 5,21% errors in misformation. Then the types of punctuation errors that dominant occur in writing recount text were period with 53,1% or 51 errors made by the eleventh grade of SMAN 14 Kabupaten Tangerang. Keywords: Error analysis, punctuation, recount text